Modeling social intelligence to achieve personal goals in agent-mediated personal knowledge management - Ismail S.; Ahmad M.S. (2023)
Personal intelligence has been coined by a number of authors and one of them relates the concept with agent-mediated personal knowledge management (PKM). The concept of agent-mediated PKM has recently been expanded to a bottom-up approach towards collective goals in organisational knowledge management (OKM). Exploiting this concept further from the perspective of crossing organisational boundaries and into the world wide web of social network, the concept of social intelligence is proposed. In this paper, a nodal approach to agent-mediated PKM is extended to model the concept of social intelligence in social network, in which knowledge workers work cooperatively with software agents in a virtual workspace called a node. This paper analyses the knowledge management processes by characterising these nodes as intelligent social entities. 2011 IEEE.